Analisis Kebutuhan E-Flipbook Keragaman Budaya Indonesia untuk Meningkatkan Hasil Belajar Siswa Kelas III Sekolah Dasar - Afifah Febrianti; Saeful Mizan; Wendri Wiratsiwi (Edukasi Elita : Jurnal Inovasi Pendidikan, 2026)
This study aims to identify the need for developing an E-Flipbook learning medium for Indonesian Cultural Diversity material in third-grade elementary school. The research was conducted because classroom instruction still relies on conventional learning media, resulting in less-than-optimal student learning outcomes. A descriptive study employing both qualitative and quantitative approaches was carried out. Data were collected through classroom observations, teacher interviews, student needs-analysis questionnaires, and pre-tests involving 22 third-grade students at UPT SD Negeri Gedongombo 1 Tuban. The findings indicate that classroom instruction remains dominated by lecture-based teaching supported mainly by printed learning materials. Teachers expressed the need for audio-visual digital learning media to improve instructional effectiveness. Questionnaire results revealed that students' demand for E-Flipbook media reached 84.5%, while the overall needs-analysis score was 76.45%, categorized as good. In addition, the average pre-test score was only 49.64, with only three students (13.6%) achieving the minimum mastery criterion (KKTP ≥75). These findings demonstrate that developing an E-Flipbook learning medium is necessary to improve students' learning outcomes on Indonesian Cultural Diversity material.